Phenology and growth of lulo (Solanum quitoense Lam) plants grafted onto Solanum hirtum Vahl. - Criollo-Escobar, Hernando; Moncayo-Palacios, Mario-Fernando; Lagos-Burbano, Tulio César (Sociedad Colombiana de Ciencias Hortícolas-SCCH and Universidad Pedagógica y Tecnológica de Colombia-UPTC, 2020)
Lulo (Solanum quitoense) is a promising Andean fruit tree that is highly valued in international markets because of its nutritional characteristics, flavor, aroma, and high content of vitamins A and C with antioxidant properties. However, certain sanitary problems, such as Fusarium oxysporum and soil nematodes, pose challenges to the competitiveness of lulo crops. Cultivating lulo plants grafted onto resistant patterns, such as S. hirtum, is a plausible solution to these sanitary issues; so, determining the behavior of grafted plants is relevant. In this study, the phenology and growth dynamics of grafted lulo plants were evaluated with functional analyses based on thermal time (degree days-DD). Completion of the vegetative phase of the lulo required 561 DD from planting to the onset of flower bud sprouting, 715 DD to reach anthesis, 801 DD for fruit set, and a cumulative total of 2,464 DD to reach fruit ripening. The functional analyses showed that Richards’s model fit the dynamics of the growth variables (height, leaf area index, crop growth index, total dry weight, leaf dry weight, and stem dry weight). Of the total plant dry biomass, 39.7% corresponded to the stems, 33.8% was from the fruits, 15.54% was from the leaves, 10.56% was from the roots, and 0.4% was from the flowers. The yield was not affected by the grafting process of lulo S. quitoense onto S. hirtum stocks; on the contrary, the crop population and productivity were maintained for a longer time.